Investigation of effects of several design parameters on exergo-sustainability metrics for twin-spool turbojet engine at different flight conditions - Aygun, Hakan (Inderscience Enterprises Ltd, 2022)
In this study, performance and exergy analyses of twin-spool turbojet engine (TS-TJE) were carried out at different flight conditions (sea level-zero Mach (phase-I) and altitude of 11,000 m-0.8 Mach (phase-II)). According to the performance analysis of TS-TJE, the rising of turbine inlet temperature (TIT) leads to increase thrust and specific fuel consumption while the increase in low pressure compressor pressure ratio (LPC PR) results in decreasing of these parameters. Moreover, overall efficiency of turbojet becomes higher due to rising LPC PR. However, the higher the TIT, the lower the overall efficiency is. On the other hand, amongst the components, exergy efficiency of the combustor has the lowest value. Considering variation of LPC PR from 2.4 to 3.4 as well as constant TIT at 1,240 K, exergy efficiency of the combustor varies from 70.87% to 73.07% at phase-I and from 75.3% to 76.7% at phase-II. On the other hand, exergetic sustainability index of TS-TJE experiences an increase from 0.265 to 0.299 at phase-I and from 0.28 to 0.302 at phase-II. It is thought that the current analysis may seem to yield new insight so as to enhance energetic and exergetic performance of turbojet engine by considering the optimum design parameters.
Keywords: two-spool turbojet; exergy; exergo-environmental; turbojet performance; exergo-sustainability